2020
DOI: 10.1021/acscombsci.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assembly and Screening of Multivalent Immune Cell-Redirecting Therapies for Leukemia

Abstract: Therapies that bind with immune cells and redirect their cytotoxic activity toward diseased cells represent a promising and versatile approach to immunotherapy with applications in cancer, lupus, and other diseases; traditional methods for discovering these therapies, however, are often time-intensive and lack the throughput of related target-based discovery approaches. Inspired by the observation that the cytokine, IL-12, can enhance antileukemic activity of the clinically approved T cell redirecting therapy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…34 Such approaches when utilized with the NIR photocaging strategy describe here may find strong utility in intravital imaging applications [24][25][26] as well as ex vivo studies of organoids and embryo-like body development where high spatial control of protein delivery is necessary for proper cell organization. 27,28 In prior work, 30,35 we demonstrated that rIL-12 could potentiate the therapeutic effects of the T cell engager, blinatumomab (Blincyto ® ) ex vivo and here we further demonstrate the NIR photo-control of this enhanced activity via NIR illumination of cCy-PEG conjugated rIL-12. This finding is significant as conventional rIL-12 therapies are wellknown to be associated with severe hematologic and hepatic toxicities that may potentially compound with those observed from blinatumomab when delivered in combination.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…34 Such approaches when utilized with the NIR photocaging strategy describe here may find strong utility in intravital imaging applications [24][25][26] as well as ex vivo studies of organoids and embryo-like body development where high spatial control of protein delivery is necessary for proper cell organization. 27,28 In prior work, 30,35 we demonstrated that rIL-12 could potentiate the therapeutic effects of the T cell engager, blinatumomab (Blincyto ® ) ex vivo and here we further demonstrate the NIR photo-control of this enhanced activity via NIR illumination of cCy-PEG conjugated rIL-12. This finding is significant as conventional rIL-12 therapies are wellknown to be associated with severe hematologic and hepatic toxicities that may potentially compound with those observed from blinatumomab when delivered in combination.…”
Section: Discussionsupporting
confidence: 61%
“…In prior work, we demonstrated that recombinant IL-12 can enhance the cytolytic activity of the T cell bispecific immunotherapy, blinatumomab, currently approved to treat patients with relapsed and refractory B cell acute lymphoblastic leukemia (B-ALL). 29, 30 To determine whether IL-12-cCy-PEG can likewise improve blinatumomab-induced cytolysis in an NIR light-dependent manner, we treated cocultures of labeled primary human CD8+ T cells and CD19+ NALM-6 B-ALL cells with blinatumomab and rIL-12 or IL-12-cCy-PEG, with and without NIR light exposure and measured CD19-specific cell lysis and T cell activation via flow cytometry and IFNγ ELISA, respectively (Figure 3a-c) . As anticipated, we observed no significant change in blinatumomab-induced cytolysis or T cell activation following co-culture with IL-12-cCy-PEG without illumination; however, following NIR LED exposure of the protein, we observed an increase in both CD19-specific lysis and IFNγ secretion that was statistically indistinguishable from that enhanced by rIL-12.…”
Section: Resultsmentioning
confidence: 99%
“…a–c) Adapted with permission. [ 67 ] Copyright 2020, American Chemical Society. d–f) Adapted with permission.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 99%
“…In a related approach, we recently developed a method to deliver IL‐12—or other cytokines—to the immunological synapse between T cells and malignant B cells via self‐assembly of antibodies about magnetic iron oxide NPs (Figures 1e and 6a–c). [ 67 ] Inspired by the clinical success of bispecific T cell engager (BiTE) immunotherapies and the challenges of IL‐12 therapy in patients, we posited that incorporation of IL‐12 onto multivalent BiTEs would both enhance anti‐tumor activity and improve upon the low half‐life of recombinant IL‐12 in circulation. To examine this hypothesis, we developed a workflow to i) generate an array of compounds with varying compositions, which we referred to as bi‐specific T cell engaging cytokines (BiTEokines), and ii) to determine ideal therapeutic candidates in a high‐throughput phenotypic screen.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 99%
“…Recent approaches to maximize the therapeutic potential of multiagent cocktails have aimed to co-deliver therapeutics in a manner that constitutively maintains drug synergy [12]; these include nanometer-scale drug carriers that deliver agents in a time-staggered [13,14] or ratiometric [15][16][17][18][19] fashion, as well as those that harness synthetic lethal gene interactions [20] or target adaptive drug resistance mechanisms a priori [21,22]. Liposomal cytarabine and daunorubicin (CPX-351, Vyxeos ® ) is one such example and was originally discovered through in vitro screens that identified synergistic cell growth inhibition at a 5:1 mole ratio of cytarabine:daunorubicin [23,24].…”
Section: Introductionmentioning
confidence: 99%